2021
DOI: 10.1024/1422-4917/a000815
|View full text |Cite
|
Sign up to set email alerts
|

Schlafverhalten und -auffälligkeiten von Kindern und Jugendlichen einer teilstationären kinder- und jugendpsychiatrischen Inanspruchnahmepopulation: Ergebnisse und Anforderungen an eine systematische Diagnostik

Abstract: Zusammenfassung. Schlafstörungen sind im Erwachsenen- wie auch im Kindes- und Jugendalter weit verbreitet. Kinder und Jugendliche in kinder- und jugendpsychiatrischer (KJP) Behandlung sind insbesondere davon betroffen. Die kognitive Verhaltenstherapie ist die Behandlung der ersten Wahl bei Schlafstörungen, der eine standardisierte Schlafdiagnostik vorangehen sollte. Im deutschsprachigen Raum fehlen bislang systematische Untersuchungen zur Schlafdiagnostik im teilstationären (TK) KJP-Setting. Für N = 46 Kinder/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Second, due to the lack of a direct control condition, we cannot rule out that the changes observed were attributable to confounding factors such as natural developmental trends. However, the 1- to 3-year stability of mental disorders in adolescents has been demonstrated in several studies, including a representative cross-sectional study in Germany consisting of almost 3000 4- to 18-year-olds, which reported no significant decreases in behavioural and emotional problems (assessed using the CBCL and YSR) with increasing age over a 2- to 3-year period (Doepfner et al ., 1997). Third, while the therapists received guidance from supervisors and had regular discussions regarding the implementation of CBT, we did not assess treatment integrity formally.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to the lack of a direct control condition, we cannot rule out that the changes observed were attributable to confounding factors such as natural developmental trends. However, the 1- to 3-year stability of mental disorders in adolescents has been demonstrated in several studies, including a representative cross-sectional study in Germany consisting of almost 3000 4- to 18-year-olds, which reported no significant decreases in behavioural and emotional problems (assessed using the CBCL and YSR) with increasing age over a 2- to 3-year period (Doepfner et al ., 1997). Third, while the therapists received guidance from supervisors and had regular discussions regarding the implementation of CBT, we did not assess treatment integrity formally.…”
Section: Discussionmentioning
confidence: 99%